Comparative evaluation of two commonly administered regimens of mifepristone and misoprostol for first trimester abortion - Devi, L. Thulasi; Nimonkar, Ravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of this study was to compare and evaluate the efficacy of two commonly administered regimens as per existing guidelines of Ministry of Health and Family Welfare for Outpatient MTP services. This study is aimed at evaluation of subjective and objective stastical benefits and side effects in performance of first trimester abortion on OPD basis in popularly used drugs as advised by MOHFW by different routes of administration. The drugs used were Tab Mifepristone (RU – 486) and Tab Misoprostol. Methods: This prospective randomized study was conducted in Out Patient Department of Obstetrics and Gynaecology in a tertiary care hospital over a period of 1 year after due clearance was obtained from Ethical Committee. This was prospective study involving 400 ladies reporting for Outpatient MTP services within the given time period as per existing guidelines at a tertiary care hospital. Patients were assessed at the end of 7, 15and 56 days, the mean age of the patients was 24.5±0.5 and 33±1 years and treatment duration was an average of 3 days with follow up for 15 days post administration. Few cases of failure required a follow up of approximately 56 days. All patients were on follow up for a period of 3 months for determination of menstrual irregularities and contraception management. Results: Between the 2 groups, in the sublingual Misoprostol group 100% aborted successfully at the end of 56 days. Whereas in the vaginal Misoprostol group 99% aborted successfully at the end of 56 days, only two patients requiring MVA as an OPD procedure. Conclusions: Patients were assessed at the end of 7, 15 and 56 days and between both the groups; Mifepristone with administration of misoprostol sublingually showed better success rate in completion of procedure, quicker action with better patient satisfaction and acceptance compared to conventional administration of Mifepristone and vaginal administration of misoprostol. Misoprostol administered sublingually under medical supervision is a superior, faster abortificient and has lesser incidence of Retained Products of Conception (RPOC) or need for Suction & Evacuation (S&E) as compared to vaginal route. Side effects observed need more evaluation with larger sample size to be statistically significant.